THE ENVIRONMENTAL IMPACT OF NATURE BASED TOURISM IN GUNUNG MERAPI NATIONAL PARK - Chafid Fandeli (Faculty of Geography, Universitas Gadjah Mada, 2008)
The goal of this research is to find out some impacts of tourism activities tothe environmental mainly to the biotic and non-biotic components. The researchalso focuses in finding out importance and performance of the products offered-byGunung Merapi National Park to the tourists. This research is done in fourlocations, consisted of the undisturbed location for controlling (Plawangan) andthe disturbed locations caused by the tourists, which are Kalikuning, Tlogonirmoloand Tlogomuncar. The result shows that the impClcts of tourist activities in somelocations show that the number of .microbial in the controlling location-is thehighest (54.56 cfu/gram) compared with others location. The impact to the numberof actin0mycetes in the controlling location is 32.84 cfu/gram, which is the highest.The infiltration rate with the model Horton in the controlling location is higher(0.983 cm/min) than the infiltration rates of the others. The voice frequencydescribes crowd level that at the controlling location has the lowest voicefrequency (10.15 dB). Some kinds of tree destruction as the impact of touristactivities show that the destructions happen mostly in Tlogomuncar, followed withKalikuning and Tlogonirmo 10. The most severe destruction of all locations isvandalism, and then scratch, spike prickling, branch breaking, and waste burning.Ihe importance and .performance of the products of the tourism objects offereddescribe that the attractions and tourism facilities like waterfall, musholla, shelter,dustbin, and observer tower have a considerable perception and goodperformance. However, some other facilities/attractions such as operational office,security center, gate, health clinique and bridge are not very important and not ina good condition.